PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP INFORMATIVENESS OF EARNING - Hermi Hermi; Dewi A Tanin (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2013)
This Research see the influence of corporate social responsibility (CSR) on the quality of works. Quality profit measured with aquamarine response koefiesien profit (ERC). Strewn do with using two-platter model regresi. The first model only menguji variables influence the CSR to ERC. Be a model both strewn do with entering the control variables growth (Growth) and lever (leveraging). Engineering sample ;Mei- is used purposive random sample, then tested with data using linear regresi. From the results found strewn that CSR has no effect on the quality of works.